Phototransformation of bisphenol a in water in the presence of materials based on ultrafine polypropylene fibers - Tchaikovskaya, Olga N.; Bocharnikova, Elena N.; Bezlepkina, N. P.; Lysak, Ilya A.; Malinovskaya, Tatyana D. 1951-; Lysak, Galina V. (Russian physics journal)
The effect of UV radiation on the efficiency of bisphenol A (BPA) phototransformation in water in the presence of polypropylene nonwoven material based on ultrafine fibers has been studied. The absorption and fluorescence spectra of the investigated substance with fibers of different properties have been obtained. After excitation with an excilamp, the main photoproduct - BPA - fluoresces in the region of similar to 408 nm. With an increase in the irradiation time from 0 to 10 min, the fluorescence intensity of this photoproduct increases. The absorption and fluorescence spectra of cyclohexane containing compounds desorbed from the fiber surface indicate the adsorption of the photoproduct on its surface during UV irradiation.